ETHICS AND SOCIAL WORK (Annual of the Faculty of Philosophy in Skopje, 2016)
Resulting from the fundamental role of the social work as an aiding profession, which is aimed to serve and assist citizens who have a certain social need, the purpose of this paper is to update the correlation between ethics and social work. In fact, the goal is to show the importance of the social workers' ethical behavior and the need for respecting ethical principles and codes of conduct, something which is neglected in our country. This can be seen by the fact that since the independence of the Republic of Macedonia, no ethical code specifically designed for social workers has been worked out.
Keywords: ETHICS; PROFESSIONAL ETHICS; SOCIAL WORK; ETHICAL PRINCIPLES; VALUES; ETHICAL CODE